Measuring citizen’s satisfaction when using E- Government online public services: Lessons from Vietnam - Thao, Nguyen Thi Phuong; Anh, Nguyen Van; Huong, Le Thi Thanh; Huy, Dinh Tran Ngoc (The journal of contemporary issues in business and government, 2021)
This study aims to evaluate the factors affecting the satisfaction of citizen when using online public services through data collected from direct surveys of people. Research results show that Quality of online public services, Citizen's awareness, Privacy and security, Trust and accessibility affect citizen's satisfaction when using online public services. Based on these results, the study also gives some discussion and governance implications for researchers as well as policy-makers in improving citizen's satisfaction as well as attracting more users for online public services in Vietnam context.